Harmattan season : a novel - Onyebuchi, Tochi (Tor, a Tom Doherty Associates book, 2025)
"Award-winning author Tochi Onyebuchi's new standalone novel is hard-boiled fantasy noir: Raymond Chandler meets P. Djèlí Clark in a postcolonial West Africa Fortune always left whatever room I walked into, which is why I don't leave my place much these days... Veteran and private eye Boubacar doesn't need much-least of all trouble-but trouble always seems to find him. Work has dried up, and he'd rather be left alone to deal with his bills as the Harmattan rolls in to coat the city in dust, but Bouba is a down on his luck deux fois, suspended between two cultures and two worlds. When a bleeding woman stumbles onto his doorway, only to vanish just as quickly, Bouba reluctantly finds himself enmeshed in the secrets of a city boiling on the brink of violence. The French occupiers are keen to keep the peace at any cost, and the indigenous dugulen have long been shattered into restless factions vying for a chance to reclaim their lost heritage and abilities. As each hardwon clue reveals horrifying new truths, Bouba may have to carve out parts of himself he's long kept hidden, and decide what he's willing to offer next. From the visionary author of Riot Baby and Goliath, Harmattan Season is a gripping fantasy noir in the tradition of Chandler, Hammond, and Christie that will have you by the throat-both dryly funny and unforgettably evocative"--